Investigating the Creativity and Its Influencing Factors among Medical Students - Amiri 1, Mohammad; Valinejad Lajimi 2, Amir; khojasteh 3, Leyla; Sadeghi 4, Zakieh; Sadeghi 5, Nafiseh; Khosravi 6, Ahmad (Shahroud Journal of Medical Sciences, 2019)
Background: Creativity is among the fundamental and constitutive features of humans, playing an important role in the development and growth of human beings and human civilization. The present study was conducted to investigate the creativity and factors influencing it among medical students.Methods: In this cross-sectional study, 320 medical students were randomly selected using stratified random sampling. Guilford's Creativity Questionnaire was used as data collection tool. Chi-Square test, and one-way analysis of Variance were used for data analysis, and the results were presented as frequency distribution tables.Results: Most of the participants (232 students (72.5%)) had moderate levels of creativity. The mean score was obtained as 49.59±5.59, 22.02± 3.29, 35.06± 4.62, 25.81±3.53, and 135.56±13.80, respectively for fluency, elaboration, originality, flexibility, and overall creativity. There was no significant relationship between overall score of creativity with gender, major, educational level, and place of residence, marital status, employment, and term of study (P≥0.05). However, there was a significant relationship between flexibility (P=0.001) and marital status (P=0.045).Conclusions: Given that about three-quarters of the participants had moderate scores while high creativity is indispensable for health care workers, educational planners need to foster this capability among the students.